Distribuição temporal e respostas celulares de Baccharis reticularia DC. (Asteraceae) a interações bióticas - Anete Teixeira Formiga (2013)
Galls are elegant models for the study of plant cell development under the influence of an external organism, the gall inducer. Although commonly occurring due to the relationship between two organisms, the host plant and the inducer, the galls may also include tritrophic or multitrophic systems. Developmental patterns observed in these systems can be evaluated through the study of structural and histochemical modifications, as well as the influence of environmental variations that result in different gall morphotypes. The plants which host different gall morphotypes are known as superhosts and are interesting for studying plant development. In these cases, different structures are developed as a result of the manipulation of the same pool of genes, under the influence of the insects stimuli vs. host plant developmentalconstraints. This study analyzes the structure and histochemistry of the gall morphotypes developed in Baccharis reticularia, focusing on the similarities between leaf and stem galls. The structural complexity of each gall is discussed under the perspective of the greater or lesser proximity to the morphogenetic pattern of their host organs. At the microscopic level, changes on the composition of the cell wall in the galls were compared using six specifically labeled epitopes: Extensins, HGAs with high and low methyl esterification, AGP glycans, galactans and arabinans. The results indicate that the stretching and flexibility potential of the plant cell wall is maintained throughout the development of the galls, and the dynamic constitution of the cell wall was, thus, proved to be crucial to their establishment. The fact that extensins were only detected in the tissues of the pocket gall morphotype is believed to be due to the greater cell elongation and flexibility required on the achievement of its final form. At the macroscopic level, two seasonal syndromes were found to be determinant for the fluctuations of the different gall morphotypes over time. Finally, the tritrophic interaction between the host plant, endophytic fungi and galling organisms positively influenced the nutritional value of plants, ensuring higher nitrogen and phosphorus content in plants bearing the kidney-shaped gall morphotype.